Integrasi Jalur Evakuasi pada Bangunan Publik Bertingkat Menggunakan Pendekatan Space Syntax: Studi Kasus: Rancangan Gedung SMP Kanisius, Kalasan - Yohanes Satyayoga Raniasta (ATRIUM: Jurnal Arsitektur, 2022)
Title: Integration of Multi-stories Public Buildings Evacuation Routes with Space Syntax Approach Case Study: The Design of Kanisius Junior High School, Kalasan   Fires and earthquakes are the two major disasters that threaten buildings. Public buildings require a design that can mitigate the adverse effects of the disaster, which requires excellent attention to the evacuation aspect when a disaster occurs. This study will evaluate the design of one of the public buildings that became the study material, Kanisius Junior High School (SMP), located in Kalasan, D.I. Yogyakarta. The building consists of 3 floors with an area per floor of 755 m2. It has a vertical emergency evacuation route through stairs at both ends. Using the Space Syntax method, the path design integration evaluation uses the Integrity tools in the Axial Map series. In contrast, the Visibility Graph tools are used to determine the level of visibility of the path and the ideal need for placing emergency exit signage. The result is that the level of integration of the evacuation route in the Kanisius Kalasan Junior High School building will be known, and the ideal signage placement will be recommended. This research is expected to contribute knowledge in the field of architecture related to the optimization method of emergency evacuation route design in multi-story buildings, as well as provide input for relevant stakeholders.